Interactive learning multimedia based on Information Communications Technologies (ICT) in analyzing electrical circuits - Radinal Fadli; Harry Pratama Figna; Indra Wijaya; Menrisal (International Conferences on Educational, Social Sciences and Technology)
Learning to Analyze Electric Circuitheld atPublic vocational high school 1 Pariaman, teachers still using conventional learning model with whiteboard and markers, this medium was only able to present the instructional in the one direction. It doesn't challenge students to understand instructionally well, so instructional goals not reached optimal.To overcome this,it need to be developed that makes students learn interactivelyand independent.In the form of interactive learning multimedia based on ICT valid, practical and effective.This is Research and Development, with the 4D model that is Define, Design, Develop and Desseminate. Based on the research results obtained data validity of the validator,1st validator 88.33%, 2ndvalidator 93.33%, and 3th88.33%, overall is valid. Test practicalities by teacher80.31%, and student 87.50%,overall is practical. The effectiveness test result is 91,89% with practical category. This research has resulted in Information Communications Technologies media isvalid, practical and effective.